Analisis Efektivitas Rotary Car Dumper (RCD) 3 dengan Metode Overall Equipment Effectiveness (OEE) di PT Bukit Asam Unit Pelabuhan Tarahan - Perwira, Rizky Agung; Wahyudi, Rizqi; Nugraha, Andhyka Tyaz (JURNAL INTEGRASI, 2024)
PT Bukit Asam Tarahan Port Unit has machines and tools that are used to assist its activities and of course indirectly support its productivity, one of these machines is the Rotary Car Dumper (RCD) 3. The Overall Equipment Effectiveness (OEE) method can identify bottlenecks in a tool or machines used in the company. Using the Six Big Losses method in this research can determine what factors make the biggest contribution resulting in the low effectiveness of using the RCD 3 machine at PT Bukit Asam Tbk Tarahan Port unit. After the losses value is obtained, the maintenance, repair and overhaul (MRO) implemented will then be analyzed and whether MRO has an effect on these losses. Based on research that has been conducted, the OEE value of the RCD 3 machine is 6%, with an average value of availability of 52%, performance of 12% and quality of 100%. The highest six big losses values were obtained from set up and adjustment losses and reduced speed losses, where the two losses obtained an average value of 46%. PT Bukit Asam Tarahan Harbor Unit has implemented planned maintenance such as preventive maintenance and corrective maintenance during the observation period from January 2021 to December 2021.